Development of CNT-Based Nanocomposites with Ohmic Heating Capability towards Self-Healing Applications in Extrusion-Based 3D Printing Technologies - Niki Loura; Eleni Gkartzou; Aikaterini-Flora Trompeta; Georgios Konstantopoulos; Panagiotis A. Klonos; Apostolos Kyritsis; Costas A. Charitidis (C, 2023)
In the present study, a series of carbon-based nanocomposites based on recycled thermoplastic polyurethane (TPU) matrix and MWCNT fillers synthesized in a laboratory environment were prepared at various loadings and assessed in terms of their functional thermal, dielectric, and rheological properties, as well as their ohmic heating capability, for self-healing applications in extrusion-based 3D printing technologies. The synthesis of nanomaterials focused on the production of two different types of carbon nanotubes (CNTs) via the chemical vapor deposition (CVD) method. A comparative assessment and benchmarking were conducted with nanocomposite filaments obtained from commercial nanomaterials and masterbatches with MWCNTs. For all the polymer nanocomposites, samples were prepared at additive contents up to 15 wt.% and filament feedstock was produced via the melt-extrusion process for 3D printing; these were previously characterized by rheological tests. The measurements of thermal and electrical conductivity resulted in a selected composition with promising ohmic heating capability. As a preliminary assessment of the self-healing ability of the above samples, artificial cracks were introduced on the surface of the samples and SEM analysis took place at the crack location before and after applying voltage as a measure of the effectiveness of the material remelting due to the Joule effect. Results indicate a promising material response with a partial restoration of artificial cracks.